2014
DOI: 10.1038/srep07442
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic 2D chirality: giant circular conversion dichroism from a metal-dielectric-metal square array

Abstract: Giant chiroptical responses routinely occur in three dimensional chiral metamaterials (MMs), but their resonance elements with complex subwavelength chiral shapes are challenging to fabricate in the optical region. Here, we propose a new paradigm for obtaining strong circular conversion dichroism (CCD) based on extrinsic 2D chirality in multilayer achiral MMs, showing that giant chiroptical response can be alternatively attained without complex structures. Our structure consists of an array of thin Au squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 48 publications
2
73
0
Order By: Relevance
“…c) Rectangular array of achiral gold nanostructures separated from a gold film by a dielectric layer. Adapted with permission . Copyright 2014, Macmillan Publshers.…”
Section: Design Of Chiral Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…c) Rectangular array of achiral gold nanostructures separated from a gold film by a dielectric layer. Adapted with permission . Copyright 2014, Macmillan Publshers.…”
Section: Design Of Chiral Materialsmentioning
confidence: 99%
“…Cao et al demonstrated, experimentally and numerically, strong circular dichroism in the mid‐IR region (∼2.4 µm), resulting from extrinsic chirality in achiral nanostructures . The structures consisted of a rectangular array of thin gold squares, separated by a dielectric layer (GaAs) atop a continuous gold film (Figure c).…”
Section: Design Of Chiral Materialsmentioning
confidence: 99%
“…Subsequently, we calculate the current distribution at resonant frequencies to further analyze the origin of asymmetric transmission, and the mode analysis based on current distribution is consistent with the magnetic field distribution . As shown in Figure 3a,b, the current density equally distributes along the sides of original metamaterials, which forms the magnetic mode perpendicular to the metamaterial surface.…”
Section: Resultsmentioning
confidence: 67%
“…Incident angle tuning is another way to manipulate the chiral response of metamaterials due to the emergent extrinsic chirality under oblique incidence . The circular dichroism (Δ=|t++|2|t0.16em|2) of metamaterials under different incident angles are calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of metamaterials makes it possible for us to obtain strong chirality. In the past few years, chiral metamaterials (CMMs) have been constructed to realize negative refractive index [15][16][17][18][19][20] , strong optical activity [21][22][23][24][25] , circular dichroism [26][27][28][29][30] , as well as asymmetric transmission [31][32][33][34][35] . Using strong resonances, the optical rotatory power of CMMs might rise up to several orders of magnitudes larger than that of natural substances [36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%